Our missing hearts : a novel - Ng, Celeste ([New York] : Random House Large Print, 2022)
In a society consumed by fear, twelve-year-old Bird Gardner, after receiving a mysterious letter, sets out on a quest to find his mother, a Chinese-American poet who left when he was nine years old, leading him to New York City, where a new act of defiance may be the beginning of much-needed change
BPL: David Winn Bishop and Isabel MacPherson Bishop Memorial Fund.
Keywords: Families -- Fiction; Chinese Americans -- Fiction; Mothers and sons -- Fiction; Racism against Asians -- Fiction; Government, Resistance to -- Fiction; Prohibited books -- United States -- Fiction; Librarians -- Fiction; Chinese Americans; Families; Government, Resistance to; Mothers and sons; Racism against Asians; Large type books; Dystopian fiction; Fiction; Novels; Psychological fiction; Dystopian fiction; Psychological fiction; Novels